2014
DOI: 10.2337/dc13-1223
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use and Utility of Integrated Electronic Health Records to Assess Rates of Prediabetes Recognition and Treatment: Brief Report From an Integrated Electronic Health Records Pilot Study

Abstract: OBJECTIVEThis study uses novel methods to examine the frequency of diagnosis and treatment of prediabetes in real-world clinical settings using electronic health record (EHR) data.RESEARCH DESIGN AND METHODSWe identified a cohort of 358,120 adults with incident prediabetes (fasting plasma glucose [FPG] 100–125 mg/dL or glycated hemoglobin 5.7–6.4% [39–46 mmol/mol]) between 2006 and 2010 and examined rates of diagnosis and treatment in the 6 months after identification.RESULTSIn the 6 months after identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
75
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 10 publications
7
75
3
Order By: Relevance
“…Although we observed a metformin prescription prevalence of 3.7%, which is higher than the prevalence of less than 0.1% previously reported by Schmittdiel and colleagues (15), it still represents underuse of a highly effective prevention strategy. Schmittdiel and colleagues only reported metformin use within 6 months of prediabetes identification, but our study examined the prevalence of metformin prescription over a 3-year study window.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Although we observed a metformin prescription prevalence of 3.7%, which is higher than the prevalence of less than 0.1% previously reported by Schmittdiel and colleagues (15), it still represents underuse of a highly effective prevention strategy. Schmittdiel and colleagues only reported metformin use within 6 months of prediabetes identification, but our study examined the prevalence of metformin prescription over a 3-year study window.…”
Section: Discussioncontrasting
confidence: 85%
“…In addition, both providers and patients may place higher priority on other medical needs or be reluctant to “medicalize” prediabetes (15). Patients and providers may also lack awareness of prediabetes, specifically the natural disease course that can result in incident diabetes in 30% of patients within 3 to 4 years (28) and the associated risks (for example, microvascular complications) (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Despite these data, 2 recent, large, managed-care database studies, the smaller of which included over 17 000 patients with newly diagnosed prediabetes, found that fewer than 4% of patients with prediabetes receive prescriptions for metformin within 3 years of diagnosis. 33,34 …”
Section: Translation Of Interventions For Diabetes Prevention Into Prmentioning
confidence: 99%
“…This anecdotal observation is congruent with literature suggesting that only 5 % of prediabetic individuals are referred to health education, wellness, or lifestyle programs. 5 Through discussion with our clinic preceptors and coresidents, we discovered that many clinicians were unaware of the NDPP and available community programs. Other physicians were aware of the NDPP, but rarely referred patients to participate, given the approximate out-of-pocket expense of $500 per participant per year.…”
mentioning
confidence: 99%